COMPARISON OF MEA, DEA AND TEA AS CO2 ABSORBENTS FOR - Waode Nur Rahmaniah; Alfian Noor; Muhammad Zakir; Maming Gaffar (Marina Chimica Acta, 2015)
Comparison of MEA, DEA and TEA as CO2 absorbent to measure carbon-14 activity of coral sample has been performed. This research aimed to Determine the age of coral reef sample of Spermonde Islands by measuring the activity of carbon-14 using the method Liquid Scintillation Counting (LSC). The sample of coral reef were collected in Langkai Island. The research were conducted by following steps of sample preparation, the CO2 absorption using the solutions of MEA, DEA and TEA. The measurement of the carbon-14 activities was performed using the Liquid Scintillation Counter (LSC) Hidex 300 SL. The research results indicated that the absorption capacities of MEA, DEA and TEA were 0.5180, 0.5903 and  the absorbents of MEA, DEA and TEA were 14.44, 14.59, and 14.42 DPM/g C respectively. The age of the coral reef sample, which was calculated based on the specific activity values using the absorbents of MEA, DEA and TEA were 480.15 ± 37; 390.11 ± 60 and 488.22 ± 87 years respectively.Keywords : LSC (Liquid Scintilation Counter), Carbon-14, CO2 Absorption, Alkanolamine, Langkai Island